MTBVAC from discovery to clinical trials in tuberculosis-endemic countries - Dessislava Marinova; Jesus Gonzalo-Asensio; Nacho Aguilo; Carlos Martin (Taylor & Francis Group, 2017)
Introduction: BCG remains the only vaccine against tuberculosis (TB) in use today and despite its impressive global coverage, the nature of BCG protection against the pulmonary forms of TB remains subject to ongoing debate. Because of the limitations of BCG, novel TB vaccine candidates have been developed and several have reached the clinical pipeline. One of these candidates is MTBVAC, the first and only TB vaccine in the clinical pipeline to date based on live-attenuated Mycobacterium tuberculosis that has successfully entered clinical evaluation, a historic milestone in human vaccinology. Areas covered: This review describes development of MTBVAC from discovery to clinical development in high burden TB-endemic countries. The preclinical experiments where MTBVAC has shown to confer improved safety and efficacy over BCG are presented and the clinical development plans for MTBVAC are revealed. The search of all supportive literature in this manuscript was carried out via Pubmed. Expert commentary: Small experimental medicine trials in humans and preclinical efficacy studies with a strong immunological component mimicking clinical trial design are considered essential by the scientific community to help identify reliable vaccine-specific correlates of protection in order to support and accelerate community-wide efficacy trials of new TB vaccines.